Microsoft 70-243 : administering and deploying System Center 2012 Configuration Manager. - Sutton, Darin; Safari eBooks ([Place of publication not identified] : Stone River eLearning, 2017)
"The new and exciting System Center 2012 Configuration Manager course provides full coverage of the knowledge and skills required to configure and manage a System Center 2012 Configuration Manager site and any associated site systems for the Configuration Manager administrator role. This new course provides you the needed training for the complete System Center Configuration Manager Infrastructure, as well as configuring roles, Central Administration Site, Secondary Site, Replication, Client Deployment, Manager Console, Manager Site, Resources and more. "--Resource description page.
Title from resource description page (Safari, viewed May 9, 2017).
Presenter, Darin Sutton.
Keywords: Microsoft System center configuration manager; Computer networks; Electronic books